2007
DOI: 10.1002/pola.21985
|View full text |Cite
|
Sign up to set email alerts
|

Original approach to multiblock copolymers via reversible addition–fragmentation chain transfer polymerization

Abstract: α,ω‐Thiol‐terminated (co)polymers synthesized via reversible addition–fragmentation chain transfer polymerization can be oxidized to yield multiblock copolymers via the formation of disulfide bridges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 31 publications
(55 reference statements)
0
74
0
Order By: Relevance
“…St [184] MMA [88] 323 [185] 40 [186] S S O O St [186] St-b-MAH [186] St-b-MAH-b-NIPAM [186] 41* [187,188] S S (MMA) [64,187,189] BA [187] EHA [188] St [190] TBAM [191] DEAM [187] DMAM [187] NAM [191] NIPAM [187,189] BA/St [192] EHA-b-MA [188] TBAM-b-NAM [191] DMAM/NAS [193] NAM-b-TBAM [191] 42* S S Ph CN MMA [194] 376 [195] 376-b-MMA [195] BA [196] MMA [189] NIPAM [189] MMA-b-NIPAM [189] MMA/283 [197] MMA/284 [197] St/2VP [198] St/348 [199] THPA-b-St [200] THPA-b-St/373 [201] 44 [202] [200] 47 [203] …”
Section: Choice Of Raft Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…St [184] MMA [88] 323 [185] 40 [186] S S O O St [186] St-b-MAH [186] St-b-MAH-b-NIPAM [186] 41* [187,188] S S (MMA) [64,187,189] BA [187] EHA [188] St [190] TBAM [191] DEAM [187] DMAM [187] NAM [191] NIPAM [187,189] BA/St [192] EHA-b-MA [188] TBAM-b-NAM [191] DMAM/NAS [193] NAM-b-TBAM [191] 42* S S Ph CN MMA [194] 376 [195] 376-b-MMA [195] BA [196] MMA [189] NIPAM [189] MMA-b-NIPAM [189] MMA/283 [197] MMA/284 [197] St/2VP [198] St/348 [199] THPA-b-St [200] THPA-b-St/373 [201] 44 [202] [200] 47 [203] …”
Section: Choice Of Raft Agentsmentioning
confidence: 99%
“…[117,130,479] This methodology has been applied to the synthesis of three-armed stars by an in-situ thiol-ene reaction with a triacrylate [130] and has been applied to directly make biopolymer conjugates. [479] A recent study shows that dithioester and trithiocarbonate RAFT agents [R-SC(S)Z] undergo a radical-catalyzed reaction with thiols that results in oxidation of the thiol to a disulfide and concomitant reduction of the RAFT agent to R-H. [481] The relative rates of reaction suggested that dithioester RAFT agents [204] PEGA Ph (58) Butylamine Used in thiol-ene [204] NIPAM SCH 2 CH(CH 3 ) 2 (188) Butylamine/TCEP/HEA butylamine/TCEP/BA One-pot thiol-ene [373] NIPAM SCH 2 CH(CH 3 ) 2 (188) Butylamine/TCEP Used in thiol-ene [371,372] NIPAM Ph (25) LiB(C 2 H 5 ) 3 H Used in thiol-ene [151] NIPAM S(CH 2 ) 2 CO 2 H (170) NaBH 4 Used in thiol-ene [355] NIPAM SC 4 H 9 (166) NaOH/MeOH/EDTA Used in thiol-ene [412] NIPAM Ph (24) Octylamine/DMPP/AMA One-pot thiol-ene [132] NIPAM Ph (24) Octylamine/DMPP/PMA One-pot thiol-ene [132] DEAM Ph (24) Hexylamine/DMPP/MA One-pot thiol-ene [130] St Ph (24) Propylamine/PBu 3 /MA NaBH 4 /PBu 3 /MA One-pot thiol-ene [117] St Ph (24) Propylamine NaBH 4 [205] MMA Ph (82) Hexylamine Conditions to favour disulfide formation [196] MMA Ph (22) Propylamine One-pot methanethiosulfonate [480] NVP OC 2 H 5 (228) NaBH 4 Used in peptide/nucleotide conjugation [396] A Monomer unit adjacent to thiocarbonylthio group. B TCEP -tris(2-carboxyethyl) phosphine hydrochloride, EDTA -ethylenediaminetetraacetic acid, TCEP -tris(2-carboxyethyl phosphine), DMPPdimethylphenylphosphine.…”
Section: Aminolysis/hydrolysis/ionic Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thiol-terminated PMMA-b-PS-SH polymers were synthesized by RAFT polymerization as previously described, [13][14][15][16] while the hydroxyl-terminated, polystyrene-deuterated polymers, dPS-b-PMMA-OH were purchased from Polymer Standards Service (Mainz, Germany). All remaining chemicals were purchased from Aldrich or Fisher, were of AR grade or better, and were used without further purification.…”
Section: Introductionmentioning
confidence: 99%
“…16 We have also described the synthesis of multiblocks comprising poly(methyl methacrylate), poly(butyl acrylate), and poly(acrylic acid). 17 Importantly, all these polymers can be reduced to the starting polymer-a reversible process.…”
Section: Introductionmentioning
confidence: 99%